PENGARUH PUPUK KASGOT BLACK SOLDIER FLY (Hermetia illucens) TERHADAP PERTUMBUHAN TANAMAN SAWI - Musyafir, Sandy; Gazali, Akhmad; Noor, Muhammad (EnviroScienteae, 2024)
This study aims to determine the effect of combining Kasgot fertilizer with dolomite on the growth and production of mustard plants, identify the best dose of Kasgot for mustard plant growth and production, and assess its impact on the properties of Ultisol soil. The study used a factorial Completely Randomized Design (CRD) with combinations of Kasgot fertilizer and dolomite, resulting in 10 treatments and 3 replications, yielding a total of 30 experimental units. M0 = NPK fertilizer at 200 kg/ha, M1 = 50 t/ha, M2 = 60 t/ha, M3 = 70 t/ha, M4 = 80 t/ha, D0 = without dolomite, D1 = with dolomite (1.4 t/ha). The results showed that applying dolomite at a dose of 1.4 t/ha (D1) significantly affected the growth of mustard plants compared to the treatment without dolomite (D0). The use of Kasgot fertilizer at a dose of 80 t/ha (M4) provided the best results for mustard plant growth, and the application of Kasgot fertilizer with dolomite was proven to improve the chemical properties of Ultisol soil, leading to increased pH, P-potential, and K-potential values.